A profissionalização do docente masculino da Educação infantil: inserção, estabilidade e atravessamentos - Bonifácio, Gabriel Hengstemberg (2019)
The present research linked to the PPGEd of UFSCar - campus Sorocaba, developed with the support of NEPEN (Center for studies and research on educational narratives, training and teaching work), has as main objective: "To point out findings, potentialities and fragilities of teacher professionalization masculine (DM) that acts in Early Childhood Education (EI) ". In order to do so, it is based on the following problem: "How is the professionalization of male teachers working in Early Childhood Education (DMEI) constituted?" The qualitative nature and methodology of Literature Review is organized in a multipaper format, two articles and final considerations. In addition, this research has its theoretical bases in authors of the field of education, which also base the analyzes. The theoretical reference refers to the discussion about perceptions about DMEI and the work on scientific research on the subject such as Apple (1988, 1995), Sayão (2005), Demartini and Antunes (1993), Kuhlmann Jr. (2000, 2010), Louro (1997, 2010, 2011), Hooks (2013) and Gambirasio (2005). Therefore, an investigation was developed in the perspective of theoretical research guided by the issues announced. With this intention, we present initially relevant aspects about the performance of these professionals, obtained from the mapping of Brazilian academic researches about their daily life in the period from 2008 to 2017, which provided an overview of the productions. This search was performed from the Brazilian Digital Library of Theses and Dissertations (BDTD) database, with the combination of the descriptors "DM" and "EI". And later in the CAPES bank, with the descriptors "Professor man" and EI. Composing the analysis corpus with 17 surveys. Based on a mapping of Brazilian academic research on the work of the DMEI, that is, the teacher teaching children at an early age, it was possible to analyze the practices from the contexts and their characteristics, promoting an expanded view of the information identified in such contexts. researches. The results obtained from the mapping of research and the problematization of the feminization of the teaching profession, the research indicates that there is a small number of researches on the DMEI, besides an amalgam of social, historical and cultural crossings.